Future Interests and the Myth of the Simple Will: An Approach to Estate Planning—Part Two - David M. Becker (Washington University Law Quarterly, 1973)
This Article stresses the extraordinary importance of anticipating the full range of problems accompanying the elaboration of any basic plan. Additionally, it develops a general approach for perceiving contingencies and eliminating oversights. The result, however, is not a “how to do it” manual for recognizing planning complexities. Although a planner is apt to encounter many of the problems raised in Part One, and might find direction from their discussion, the analysis of selected problems in Part One was illustrative only. Part Two, however, suggests an approach to problems which goes beyond those previously discussed; once again the emphasis is upon effective “prevision.”
Keywords: Wills and Estates